Peripheral proteinopathy in neurodegenerative diseases - Bin Xu; Xia Lei; Ying Yang; Jiayi Yu; Jun Chen; Zhi Xu; Keqiang Ye; Jing Zhang (Translational Neurodegeneration)
Abstract Proteinopathies in neurology typically refer to pathological changes in proteins associated with neurological diseases, such as the aggregation of amyloid β and Tau in Alzheimer’s disease, α-synuclein in Parkinson’s disease and multiple system atrophy, and TAR DNA-binding protein 43 in amyotrophic lateral sclerosis and frontotemporal dementia. Interestingly, these proteins are also commonly found in peripheral tissues, raising important questions about their roles in neurological disorders. Multiple studies have shown that peripherally derived pathological proteins not only travel to the brain through various routes, aggravating brain pathology, but also contribute significantly to peripheral dysfunction, highlighting their crucial impact on neurological diseases. Investigating how these peripherally derived proteins influence the progression of neurological disorders could open new horizons for achieving early diagnosis and treatment. This review summarizes the distribution, transportation pathways, and pathogenic mechanisms of several neurodegenerative disease-related pathological proteins in the periphery, proposing that targeting these peripheral pathological proteins could be a promising strategy for preventing and managing neurological diseases.